Pengaruh Game Edukasi Berbasis Kearifan Lokal Berorientasi Terhadap Keterampilan Menulis Siswa di Sekolah Dasar - Linaria Arofatul Ilmi Uswatun Khasanah (Elementary Teacher Education Program, Majalengka University, 2023)
The use of vocabulary used in local wisdom learning often has errors that make it difficult for students to understand the material, besides the use of media that is less interesting makes students less interested in the learning process. This study aims to determine the effect of using local wisdom-based educational games on students' writing skills in elementary school. This research is a quantitative study using experimental research methods with the form of true experimental design. The sampling technique in this study was simple random sampling technique with the lottery of grade 1 SDN Jetis 4 Lamongan. This study used a pretest-posttest control group design. The research subjects were grade 1 students of SDN Jetis 4 Lamongan. In this study the research subjects were divided into two groups, namely the experimental group and the control group. The data analysis technique used is hypothesis testing which consists of normality test, homogeneity test, and T test. İnstruments used in this study are in the form of description questions that help students in improving writing skills. Based on these results. Based on these results, it can be concluded that educational games based on local wisdom are very influential on students' writing skills in elementary schools